Preparation and characterization of hydrogels from polyvinyl alcohol and cellulose and their electroactive behavior. Issue 1 (2nd January 2017) - Jayaramudu, Tippabattini; Ko, Hyun-U; Zhai, Lindong; Li, Yaguang; Kim, Jaehwan
ABSTRACT: This paper reports polyvinyl alcohol/cellulose-based electroactive hydrogels for actuator applications. The polyvinyl alcohol/cellulose electroactive hydrogels were obtained by physical crosslinking of polyvinyl alcohol and cellulose. The formation of the polyvinyl alcohol/cellulose hydrogel structure, its thermal stability, crystallinity, and mechanical properties were studied by using the Fourier transform infrared spectroscopy, scanning electron microscopy, thermogravimetric analysis, differential scanning calorimetry, X-ray diffraction, and mechanical test. The studies reveal that the cellulose is uniformly reacted with hydroxyl groups of polyvinyl alcohol by intermolecular bond formation. The cellulose content along with actuation voltage and frequency of electroactive hydrogels influence their displacement behavior.